PEMETAAN DAERAH RAWAN KEBAKARAN HUTAN DAN LAHAN DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (STUDI KASUS: KECAMATAN BUKIT BATU, KAB. BENGKALIS) - Putra, Ajriansyah; Ratnaningsih, Ambar Tri; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
This study aims to map the level of vulnerability of forest and land fires in an effort to support the realization of forest fire management strategy in Bengkalis Regency by considering land cover aspects, soil type, rainfall, height of place and settlement distance. This research was conducted in Bukit Batu sub-district, Kab. Bengkalis. This research uses survey method in collecting secondary data and primary data. The data analysis was done with each observation parameter. The results of this study indicate that the level of fire vulnerability in Bukit Batu Subdistrict is divided into two classes, namely very high and high vulnerability. Most of Bukit Batu sub-district has a very high level of vulnerability. High vulnerability area has 27,533,611 Ha (22,49%) and very high 94,915,83 (77,51%). Where the determining factor that plays a major role in influencing the high level of vulnerability in a location that is land cover, rainfall, and soil type.